EMPLOYABILIİTY FORECASTING SCALE: VALIDITY AND RELIABILITY STUDY (Third Sector Social Economic Review, 2023)
The aim of this study is to develop the Employability Forecasting Scale and to test its validity and reliability. In the study, first of all, a literature review was conducted and an item pool was created, including 39 items. In order to ensure the content validity of the item pool, 11 experts working in the field of social policy were consulted. Various revisions were made in the scale items in line with the feedback received from the experts and a draft scale with 37 items was obtained. Exploratory factor analysis (EFA) was performed by applying the draft scale on 521 samples of senior university students. Confirmatory factor analysis (CFA) was performed by applying the scale structure formed after EFA on 384 samples. In this context, the scale structure formed as a result of EFA was tested with CFA, its compatibility was checked and its validity was ensured. The reliability of the scale was analyzed with the Cronbach Alpha coefficient over internal consistency. SPSS 22 and SPSS AMOS programs were used in the analysis of the data. According to the findings obtained from the study; The Employability Forecasting Scale is a scale that can be used in related research, providing adequate psychometric properties and a high degree of validity and reliability.
Keywords: Employability; Validity and Reliability; Exploratory Factor Analysis; Confirmatory Factor Analysis; Scale Development.